THEORY AND LEGALITY OF MUDHARABAH FINANCING IN INDONESIAN ISLAMIC FINANCIAL INSTITUTIONS - Fadhil Muhammad (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Islamic financial institutions continue to experience very rapid development, one of the contracts that is often carried out is the mudharabah contract and as a form of state law, legality and regulation are important things to create in order to have a strong foundation. The purpose of this article, to see the extent of legality and regulation in mudharabah contracts. the author uses library research methods (library research), this research is quantitative research and this research uses two types of legal materials, consisting of primary legal materials and secondary legal materials. The results found in this article, namely the legality and regulation under the protection of the state can be said to be very strong because this regulation is already contained in the legislation, the Fatwa of the National Sharia Council - Indonesian Ulema Council (DSN-MUI), and regulations from the Financial Services Authority (OJK) and in accordance with maqashid sharia, especially in protecting assets (Hifdzu Al-Maal) by avoiding things that are prohibited in muamalah which makes customers feel comfortable and not worried.